Strategi Store Atmosphere Untuk Meningkatkan Kepuasan Konsumen Di Restoran Cepat Saji X - M. Albi Sahal Ma'hadi; Endang Silaningsih; Riva Aryani Putri; Rian Permana; Adhitia Maulana (MIZANIA: Jurnal Ekonomi Dan Akuntansi, 2024)
This study analyzes the role of store atmosphere in enhancing customer satisfaction at Fast Food Restaurant X and identifies the most influential atmospheric elements. Using a quantitative approach with Importance Performance Analysis (IPA), the study evaluates the gap between customer expectations and reality based on a sample of 50 respondents. The results indicate that environmental comfort, interior color, and lighting are highly important but underperforming. Meanwhile, cleanliness, signage clarity, and store layout meet customer expectations. This study highlights that restaurant atmosphere design is not merely an aesthetic factor but a strategic element that enhances customer satisfaction and business competitiveness. Managerial implications include improving interior design, optimizing lighting, and refining spatial layout to create a better customer experience. Additionally, the study opens opportunities for further research on the long-term impact of store atmosphere on brand loyalty.